Impact of eHealth education to reduce anemia among school-going adolescent girls in rural Bangladesh: Study protocol of a randomized controlled trial - Md Jiaur Rahman; Md Moshiur Rahman; Masayuki Kakehashi; Ryota Matsuyama; Mohammad Habibur Rahman Sarker; Mohammad Ali; Sumaita Kabir Promitee; Junaidi Budi Prihanto; Ashir Ahmed; Yoko Shimpuku (Journal of Family Medicine and Primary Care)
Adolescent girls are highly vulnerable to developing anemia due to reproductive immaturity, poor personal hygiene, and lack of nutritional intake and health education in rural Bangladesh. Digital health technology is a promising tool to overcome barriers and provide appropriate health guidelines. We aim to evaluate eHealth education's impact and changes in adolescent girls' knowledge, attitude, and practice regarding anemia. A 1:1 parallel randomized control trial was conducted among school-going adolescent girls in rural Bangladesh. A total of 138 anemic (mild and moderate) participants were enrolled. We randomized schools to reduce the health education bias through a simple coin toss technique, then allocated participants to the intervention group (n = 69) and control group (n = 69) by stratified random sampling technique. The intervention group received two online counseling sessions and 8-month eHealth education through mobile phone calls and short message service regarding anemia. The control group received the usual care. The primary endpoint changes the anemic level through changing knowledge, healthy lifestyle behavior, and an iron-rich food dietary plan. Per-protocol analysis will utilize to compare the control and intervention groups using SPSS software. Descriptive statistics (frequencies, percentages, mean, SD) will be employed, and continuous variables will be compared using the t-test/Mann–Whitney test. Two-way analysis of variance will assess outcome variables at baseline, 4 months, and 8 months. The 8-month intervention is designed from May 2022 to February 2023. Participants' age range of 10-14 years was 60.9% in the intervention group and 56.5% in the control group. Among the participants, 89.9% and 88.4% were mild anemic; 11.11 (SD ± 0.80) and 11.06 (SD ± 0.96) were mean hemoglobin in the intervention and control groups, respectively. eHealth education is expected to be an effective way to increase knowledge and healthy behavioral change, which can reduce the anemia burden among adolescent girls.